Effects of short-term phosphate loading on aerobic capacity under acute hypoxia in cyclists: A randomized, placebo-controlled, crossover study - Ploszczyca, K.; Chalimoniuk, M.; Przybylska, I.; Czuba, M. (Nutrients, 2022)
The aim of this study was to evaluate the effects of sodium phosphate (SP) supplementation on aerobic capacity in hypoxia. Twenty-four trained male cyclists received SP (50 mg·kg-1 of FFM/day) or placebo for six days in a randomized, crossover study, with a three-week washout period between supplementation phases. Before and after each supplementation phase, the subjects performed an incremental exercise test to exhaustion in hypoxia (FiO2 = 16%). Additionally, the levels of 2,3-diphosphoglycerate (2,3-DPG), hypoxia-inducible factor 1 alpha (HIF-1a), inorganic phosphate (Pi), calcium (Ca), parathyroid hormone (PTH) and acid-base balance were determined. The results showed that phosphate loading significantly increased the Pi level by 9.0%, whereas 2,3-DPG levels, hemoglobin oxygen affinity, buffering capacity and myocardial efficiency remained unchanged. The aerobic capacity in hypoxia was not improved following SP. Additionally, our data revealed high inter-individual variability in response to SP. Therefore, the participants were grouped as Responders and Non-Responders. In the Responders, a significant increase in aerobic performance in the range of 3-5% was observed. In conclusion, SP supplementation is not an ergogenic aid for aerobic capacity in hypoxia. However, in certain individuals, some benefits can be expected, but mainly in athletes with less training-induced central and/or peripheral adaptation.